2004
DOI: 10.1016/j.ydbio.2004.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the head–trunk interface for the neural crest

Abstract: The head-trunk interface lies at the occipito-cervical boundary, which corresponds to the somite 5/6 level. Previous studies have demonstrated that neural crest cells also behave differently either side of this boundary and that this may be due to intrinsic differences between cranial and trunk crest. However, it is also possible that some of the observed differences between cranial and trunk crest are assigned by environmental cues. We have therefore scrutinised the behaviour of the neural crest cells generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Studies using chick embryos suggest that cranial paraxial mesoderm is able to direct CNC cell movement independently of their epithelial or mesenchymal organization (Noden, 1986;Ferguson and Graham, 2004). Of interest, recent cell fate mapping analysis has suggested that myoblast precursors contain positional identity inherited from their somatic mesenchymal stem cell precursors and can help to determine skeletal homologies that are based on muscle attachments (Matsuoka et al, 2005).…”
Section: Mesodermmentioning
confidence: 99%
“…Studies using chick embryos suggest that cranial paraxial mesoderm is able to direct CNC cell movement independently of their epithelial or mesenchymal organization (Noden, 1986;Ferguson and Graham, 2004). Of interest, recent cell fate mapping analysis has suggested that myoblast precursors contain positional identity inherited from their somatic mesenchymal stem cell precursors and can help to determine skeletal homologies that are based on muscle attachments (Matsuoka et al, 2005).…”
Section: Mesodermmentioning
confidence: 99%
“…Somites impose many spatial constraints upon the pathways available to migrating neural crest cells (Loring and Erickson, 1987;Kalcheim and Tiellet, 1989;Ferguson and Graham, 2004) and preclude the dissemination of large connective tissue-forming crest populations. This becomes especially problematic in unraveling the homologies in amniotes of muscles associated with ancestral caudal gill arches, which formed at the same axial levels as the rostral somites but (presumably) derived their connective tissues from the neural crest.…”
Section: Occipital Somites and The Somite-presomitic Mesoderm Boundarymentioning
confidence: 99%
“…Studies in chickens and mice show that NC cell fates are influenced by signals emanating from their host tissues (Chen et al, 2012;Donoghue et al, 2008;Ferguson and Graham, 2004;Itasaki et al, 1996;Trainor and Krumlauf, 2000;Trainor et al, 2002a,b). In the pharyngeal arches, Notch signaling from the PAA endothelium mediates differentiation of the adjacent NC cell layers into VSMCs, and the region of active Notch around the PAA endothelium corresponds to the area within which NC cells undergo VSMC differentiation (High et al, , 2007Manderfield et al, 2012).…”
Section: Introductionmentioning
confidence: 99%